Disparities in Patient Outcomes After Elective Lumbar Fusions in Single-Level Lumbar Disc Pathologies. (1st September 2019) - Reddy, Abhinav K; Ostrov, Philip B; Ryoo, James S; Kim, Soobin; Mehta, Ankit Indravadan
Abstract: INTRODUCTION: Previous work has shown that disparities exist in fusion rates after decompression of single-level lumbar disc herniation or degeneration in terms of patient demographics and hospital characteristics. This study seeks to observe disparities in patient-centered outcomes for those receiving fusions after elective decompression for single-level disc pathologies. METHODS: Patients requiring elective surgical treatment for single-level disc pathologies were queried from the National Inpatient Sample datasets spanning 2012 to 2015. Multivariate logistic and linear regressions (Holm-Bonferroni corrected) were performed to assess effects of patient demographics, temporality of admission, and hospital demographics on rates of nonhome discharge, length of stay (LOS), and LOS-adjusted total charges in patients who received lumbar fusion with decompression (laminectomy and/or discectomy) while controlling for patient-level medical comorbidities. RESULTS: A total of 39 076 patients were included in the outcome analysis of fusion after elective surgical intervention for lumbar disc pathologies. Black and Hispanic patients stayed in the hospital 0.37 and 0.17 d longer ( P < .001 and P = .007), respectively, and were more likely to have a non-home discharge (OR 1.88, P < .001; OR 1.48, P < .001, respectively) compared to White patients. Compared to smaller hospitals, medium and large hospitals charged 5908.99 and 10, 895.07 more per day, respectively ( P < .001), stayed in the hospital 0.16 and 0.38 d longer, respectively ( P < .001), and had more nonhome discharges (OR 1.22, P = .008; OR 1.30, P < .001, respectively). Urban teaching hospitals were associated with a 0.53 d increase in LOS ( P < .001) and higher odds of nonhome discharge (OR 1.38, P = .015) compared to rural hospitals. CONCLUSION: The results of this study illustrate disparities in patient-centered outcomes after surgical intervention of lumbar disc pathologies based on elective lumbar fusion.